Effect of solid solution rare earth (La, Ce, Y) on the mechanical properties of α-Fe - Bai Chunying; Bai Guojun; Liu Xiangjun; Wang Ting (High Temperature Materials and Processes)
In view of the fact that the current experimental method is not very satisfactory to study the solid solution behavior of rare earth elements (RE) in steel, it is an effective and economical method to replace the experimental research with the simulation calculation method. In this article, the Fe-RE (La, Ce, Y) systems were constructed based on the density functional theory, and mechanical properties of doping systems were calculated. The calculation results of the solvation energy show that La, Ce, and Y can form stable solid solutions in α-Fe, and Ce has the highest solid solubility in α-Fe, followed by Y and La. The results of elastic moduli show that the doping of RE (La, Ce, Y) reduces the incompressibility, shear strain resistance, stiffness, and Vickers hardness of the doping system, while increasing the toughness and machinability. The strength properties of the doping systems are Fe–Ce > Fe–La > Fe–Y, and the toughness and machinability are opposite. In Fe–RE (La, Ce, Y) doping systems, RE (La, Ce, Y) reduce the metal bond strength of the Fe system, which is the fundamental reason for the decrease of the strength properties of the doping system. In addition, in doping system, Fe atoms gain electrons and RE (La, Ce, Y) atoms lose electrons. And the increase of electron cloud density in the doping system can be used to explain the improvement of toughness and machinability of the system.